2022
DOI: 10.1167/jov.22.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Stereo slant discrimination of planar 3D surfaces: Frontoparallel versus planar matching

Abstract: Binocular stereo cues are important for discriminating 3D surface orientation, especially at near distances. We devised a single-interval task where observers discriminated the slant of a densely textured planar test surface relative to a textured planar surround reference surface. Although surfaces were rendered with correct perspective, the stimuli were designed so that the binocular cues dominated performance. Slant discrimination performance was measured as a function of the reference slant and the level o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Although this section has been based on the geometry of space curves and their projections, we observe that related geometric approaches have been developed for planar patches and surfaces; see, e.g., Li and Zucker, 2008;Oluk et al, 2022 and references therein.…”
Section: Tangent Estimationmentioning
confidence: 99%
“…Although this section has been based on the geometry of space curves and their projections, we observe that related geometric approaches have been developed for planar patches and surfaces; see, e.g., Li and Zucker, 2008;Oluk et al, 2022 and references therein.…”
Section: Tangent Estimationmentioning
confidence: 99%
“…And this includes the ground plane surface. Recent work on the modeling of binocular stereopsis has shown that correlational algorithms based on the matching of local surface patches are more successful than conventional point-based solutions (Banks et al, 2004;Oluk et al, 2022). It is rather ironic that Bela Julesz's attempt to model the processing of binocular disparities 50 years ago was essentially a correlational algorithm (Julesz, 1971).…”
Section: The Correspondence Problemmentioning
confidence: 99%
“…In other words, we are still describing the correspondence (or lack of correspondence) between individual points or features in the two optic arrays or the retinal images (e.g., Read et al, 2009 ). A quite different approach is to think about how the optic array created by a surface (rather than points or features) is transformed or mapped from one (binocular) optic array to the other ( Banks et al, 2004 ; Michaels & Carello, 1981 ; Oluk et al, 2022 ). The simplest example of such a transformation is in the viewing of a surface that lies at an eccentric location with respect to the two binocular vantage points: that is, off to one side.…”
Section: Further Misconceptions About 3d Visionmentioning
confidence: 99%
“…The perceived slant of a random-dot stereoscopic surface is altered by the presence of a surrounding slanted surface, a phenomenon termed stereo slant contrast ( Gillam & Pianta, 2005 ; Goutcher & Wilcox, 2021 ; Graham & Rogers, 1982 ; Poom, Olsson, & Börjesson 2007 ; Rogers, Cagenello, & Rogers, 1988 ; van der Kooij & te Pas, 2009a ; van der Kooij & te Pas, 2009b ; van Ee, Banks, & Backus, 1999 ; Wardle & Gillam, 2016 ; reviewed in Howard & Rogers, 2002 ). Here, we use the term “slant” to characterize a planar surface oriented around the horizontal axis (as, for example, in Oluk, Bonnen, Burge, Cormack, & Giesler, 2022 )—in other words, an inclination (although note that others have defined “slant” as a surface oriented around a vertical axis and hence distinct from inclination; e.g., Howard & Rogers, 2002 ). Stereo slant contrast is “bidirectional” in that the perceived slant of the test surface is invariably shifted away from that of the surround surface (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%